Quranic Literacy Culture as a Strategy for Strengthening Students' Religious Identity in Higher Education During Digital Disruption - Pangesti, Maria Ulfa Dwi (Generate Digital Publishing, 2026)
Objective: This study aims to analyze the role of Al-Qur'an literacy culture in strengthening students' religious identity amid technological disruption and to formulate a Qur'anic literacy development model relevant to the digital age. Research Design & Methods: This study employs a qualitative descriptive approach combined with a systematic literature review using the PRISMA protocol. A total of 13 articles published between 2019 and 2024 were selected through a rigorous process of identification, screening, eligibility, and synthesis. Findings: The findings reveal that technological disruption has a dual impact on students’ religious identity. On one hand, it creates challenges such as fragmented attention, conflicting values, weakened traditional authority, and performative religiosity. On the other hand, it offers opportunities including broader access to religious knowledge, virtual communities, personalized learning, and digital da'wah innovation. The study proposes a five-level Al-Qur'an literacy ecosystem consisting of institutional policy, curriculum, infrastructure, mentoring, and campus culture, and introduces the concept of mixed religiosity integrating online and offline practices. Contributions: This study provides practical implications for higher education institutions to develop an integrated Qur'anic literacy ecosystem that is adaptive to digital transformation, including strengthening institutional policies, curriculum innovation, and technology-based religious learning. Novelty: The novelty of this study lies in the development of an integrated analytical model of Qur'anic literacy that combines multidimensional literacy, hybrid religiosity, religious identity, and digital technology perspectives.